Isolation of Antibacterial Depside Constituents from Indonesian Folious Lichen, Candelaria fibrosa. Issue 1 (2nd January 2022) - Nugraha, Ari Satia; Dayli, Ikhar Ridho; Sukrisno Putri, Chintya Permata Zahky; Firli, Lilla Nur; Widhi Pratama, Antonius Nugraha; Triatmoko, Bawon; Untari, Ludmilla Fitri; Wongso, Hendris; Keller, Paul A.; Wangchuk, Phurpa
Abstract: There is an urgent need for novel drug leads, especially for microbial infections due to continuing emergence of drug resistance. Natural products are the backbone of modern medicine and the lichens have an important role to play in the discovery of novel drugs. Indonesia is gifted with a diverse array of lichens, which remain underexplored for medicinal applications. In this study, we have collected a lichen, Candelaria fibrosa, and conducted phytochemical and bioactivity studies. Using high performance liquid chromatography, mass spectrometry, and nuclear magnetic resonance spectroscopy, we have isolated and characterised two depside compounds, atraric acid (7) and methyl 3-hydroxy orsellinate (8). These two depsides were reported from this lichen species for the first time. The evaluation of the crude methanol extract against Gram-positive bacteria, Staphylococcus aureus, indicated insignificant activity. However, the isolated compounds have been previously reported to possess low antimicrobial activity against common pathogenic bacteria ( Staphylococcus aureus, Bacillus cereus and Pseudomonas aeruginosa ) but to show significant anti-legionellosis. Graphical abstract: UF0001